Masterpieces of Kabuki : eighteen plays on stage - Brandon, James R.; Leiter, Samuel L. (Honolulu : University of Hawai'i Press, 2004)
Masterpieces of Kabuki contains eighteen outstanding dramas taken from the landmark four-volume series Kabuki Plays On Stage. Together they cover the entire spectrum of kabuki drama from 1697 to 1905, the period during which kabuki's dramaturgy flourished prior to the onset of Western dramatic influence. Major playwrights, chronological periods of playwriting, and a variety of play types (history, domestic, and dance dramas) and performance styles are represented. All but one are in the current repertory and regularly staged. The volume includes introductions to each play and a new general introduction highlighting kabuki's historical development and relating the plays to their performance context. As the subtitle implies, the plays are translated as if "on stage." Stage directions indicate major scenic effects, stage action, costuming, makeup, music, and sound effects. In some cases, complex stage actions such as stage fights are given in detail. The plays collected here are all marvelous examples of dramatic writing, intended to be acted on the stage before audiences. They reveal kabuki's eras of brilliance and bravado, villainy and vengeance, darkness and desire, and restoration and reform. All continue to stir audiences to admiration and excitement
Frontmatter -- Contents -- Preface -- Introduction / Brandon, James R. / Leiter, Samuel L. -- Just a Minute! Shibaraku / Saltzman-Li, Katherine -- The Stone-Cutting Feat of Kajiwara Kajiwara Heizò Homare no Ishikiri From Miura no Òsuke Kòbai Tazuna The Plum-Blossom Reins of Miura no Òsuke / Lee, William -- Summer Festival: Mirror of Osaka Natsu Matsuri Naniwa Kagami / Iezzi, Julie A. -- Japan's Twenty-Four Paragons of Filial Piety Honchò Nijûshikò / Griffith, Paul M. -- The Precious Incense and Autumn Flowers of Sendai Meiboku Sendai Hagi / Johnson, Matthew -- The Revenge at Tengajaya Katakiuchi Tengajayamura / Cummings, Alan -- A Message of Love from Yamato Koi Tayori Yamato Òrai / Brandon, James R. -- The Picture Book of the Taikò Ehon Taikòki / Leiter, Samuel L. -- The Scandalous Love of Osome and Hisamatsu Osome Hisamatsu Ukina no Yomiuri / Durham, Valerie L. -- Kasane / Oshima, Mark -- Masakado / Pronko, Leonard C. -- The Tale of the Martyr of Sakura Sakura Giminden / Philips, Anne -- The Three Kichisas and the New Year's First Visit to the Pleasure Quarters Sannin Kichisa Kuruwa no Hatsugai / Hibino, Kei / Cummings, Alan -- The Fishmonger Sògorò Sakanaya Sògorò FROM Shin Sarayashiki Tsuki no Amagasa Moonlit Umbrella at the Dish Palace, New Version / Bach, Faith -- The Mirror Lion, A Spring Diversion Shunkyò Kagami Jishi / Griffith, Paul M. / Rimer, J . Thomas -- Glossary -- Selected Bibliography -- Contributors -- Index -- List of Plays in Kabuki Plays on Stage
In English.
Online resource; title from digital title page (viewed on January 28, 2020).
Includes bibliographical references and index.
JSTOR
Keywords: Kabuki plays -- Translations into English; DRAMA -- Asian -- General; Kabuki plays; Translations